ALIH TEKNOLOGI DALAM UPAYA MENINGKATKAN PRODUKTIVITAS DAN PROFITABILITAS USAHA RUMAHAN “NAURAH CAKES” - Adhe Anggry; Shanty Dwi Krisnaningsih (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Home businesses are part of UMKM whose existence is very useful in improving the national economy, one of which is in the distribution of the people's income. This science and technology for society (IbM) activity targets home business called